Persepsi Petani Padi terhadap Program Billing System di Kecamatan Candipuro Kabupaten Lampung Selatan - Hutagalung, Andreas Dolar; Nurmayasari, Indah; Yanfika, Helvi (Suluh Pembangunan : Journal of Extension and Development, 2021)
This research aims to determine the perception of rice farmers on the Billing System program, the factors related to the farmers' perceptions of the Billing System program. This research was conducted in Candipuro District, South Lampung Regency. The research location was chosen purposively with the consideration that Candipuro District was the first sub-district to implement the Billing System program. This study used a survey method and obtained a sample of 30 rice farmers. Data analysis in this research was carried out by descriptive analysis with a quantitative approach. The results showed that rice farmers' perceptions of the Billing System program were classified as moderate, which with the program, farmers felt that there wasn't a delay in the distribution of fertilizers, the number of fertilizer needs fulfilling, the existence of this program made farmers being proactive in groups, and with the program very influential in increasing production yields and increasing farmers' income. Factors related to farmers' perceptions are the level of knowledge (X₂) and level of motivation (X₃), while the level of education (X₁), length of farming (X₄), and land area (X₅) are not related.